2003
DOI: 10.1029/2003jd003651
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term climate variations in China and global warming signals

Abstract: [1] In this work, the authors analyze the observed long-term variations of seasonal climate in China and then investigate the possible influence of increases in greenhouse gas concentrations on these variations by comparing the observations with the simulations of the second phase of the Coupled Model Intercomparison Project (CMIP2). The long-term variations of precipitation and temperature in China are highly seasonally dependent. The main characteristic of summer precipitation in China is a drying trend in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
212
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(236 citation statements)
references
References 30 publications
21
212
1
2
Order By: Relevance
“…Because our analysis is based on an updated dataset from 1961−2007, the results obtained here are somewhat different from those of earlier works based on data during 1951−2000 (Hu et al, 2003;Zhai et al, 2005). For instance, although positive trends of total winter precipitation could still be recognized over Tibet and southern China during the earlier period, the previous authors noted significant negative trends over most parts of northeast and North China in winter.…”
Section: Conclusion and Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Because our analysis is based on an updated dataset from 1961−2007, the results obtained here are somewhat different from those of earlier works based on data during 1951−2000 (Hu et al, 2003;Zhai et al, 2005). For instance, although positive trends of total winter precipitation could still be recognized over Tibet and southern China during the earlier period, the previous authors noted significant negative trends over most parts of northeast and North China in winter.…”
Section: Conclusion and Discussioncontrasting
confidence: 55%
“…This is in agreement with earlier findings. Hu et al (2003) found that during the second half of the 20th century, drying trends appeared mainly along the mid-lower reaches of the Yangtze River, and wetting trends were found in parts of northeast and north China in spring. Zhou and Huang (2006) noticed a reverse interdecadal variation between spring and summer precipitation in northern China.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the East Asian summer monsoon (EASM) has weakened since the late 1970s, which is characterized by the weakening of the 850 hPa southwesterly winds, southward shift of the 200 hPa jet stream, and increases in sea level pressure over East Asia (Hu 1997;Wang 2001;Guo et al 2003;Hu et al 2003;Wang and Ding 2006;Xu et al 2006). Furthermore, a cooling trend in the upper troposphere and lower stratosphere over East Asia has led to the weakening in the northward progression of southerly monsoon winds over this region Yu and Zhou 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Xin et al (2006) noticed the strengthening of the droughts during late spring (20 April-20 May) since 1981 in regions near the Yangtze River. Hu et al (2003) and Zhai et al (2005) indicated the recent decreased precipitation in this region during spring. However, research results indicating the contrary have also been reported; they state that the frequency and strength of extreme precipitation in the southeast midlower reaches of the Yangtze River have increased since the early 1980s (Buda et al, 2007).…”
Section: Introductionmentioning
confidence: 99%